Treating amine contaminated wastewater using activated sludge in sequencing batch reactor - Ungku Amirah Najihah, Ungku Mohd Haddad (2024)
Several industrial sectors that serve as significant sources of amine emissions into the environment, with particular emphasis on the release of amines in effluent streams. These industries span a diverse range, such as petrochemical, pharmaceutical, and wastewater treatment plants. Previous research showed that amine may be eliminated using chemical, biological, and physical methods. Despite their potential for great removal efficiency, physicochemical and chemical treatments are still restricted due to their high operating costs and limited use in small-scale facilities. On the other hand, because of its adaptability and low cost of operation, a biological approach could be the ideal choice. Therefore, the purpose of this study is to determine if eliminating amines from synthetic wastewater using an aerobic biological treatment in a sequencing batch reactor (SBR) is feasible. 3.25L of SBR that had been inoculated with sludge from palm oil mills served as the substrate for the experiment. The synthetic wastewater was fed in the reactor and ethanolamine was added as a source of amine with initial concentration between 300 and 500 mg/L. After 48 days of operation, the present SBR simultaneously removed amine and COD with removal efficiencies of higher than 99% and 90%, respectively. At the end of operation, the concentration of solid in effluent was around 80 mg/L which comply with the DOE requirement. In conclusion, the aerobic activated sludge technology has the ability to simultaneously remove wastewater containing amine and COD with high removal efficiency. Besides, the microbial communities within activated sludge can perform both aerobic and anaerobic processes, enabling the effective removal of nitrate from amine wastewater. Thus, application of this technology to the real wastewater from petrochemical, tannery and photographic is highly recommended.